(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this article I deal with the reception of political theater, as well as the discourses produced by specialized journalistic and academic critics. I maintain that a vast area of contemporary political theater that addresses the last dictatorship in Argentina proposes an absolutely active kind of ideal spectator. In pursuit of shocking and challenging the spectator, contemporary theater that refers to the 1970s questions the place that the spectator occupies facing state terrorism. The plays that are analyzed in this work are attempts to undermine the immutability of the viewer in front of the consequences of dictatorial terror, confronting and testing the social knowledge of spectators with the knowledge specific of the text.